Tailoring of Structural and Optical Properties of ZnO Nanoparticles by Co Doping - Arshad, Mohd; Azam, Ameer; S. Ahmed, Arham; Mollah, S.; H. Naqvi, Alim (Asian Journal of Chemistry, 2011)
Pure and Co doped ZnO nanoparticles have been synthesized by wet chemical route and characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM), transmission electron microscopy (TEM), energy dispersive X-ray analysis (EDAX), UV-visible absorption spectroscopy and Fourier transform infrared spectroscopy (FTIR). X-ray diffraction analysis revealed the formation of single phase structure of all samples which was further supported by FTIR data. Crystallite size observed 27.1 for 0 % and 21.3 nm for 5 % Co concentration, suggesting the prevention of crystal growth with Co doping. It was clear from the absorption spectra that the absorbance tends to increase with the increase in dopant concentration. Optical band gap was calculated using Tauc relation and found to increase slightly with the increase in Co contents, confirming the size reduction as a result of Co doping.